TD Fratello Enterprise / Mohd Wishal Nasrullah Azahar ... [et.al.]. - Azahar, Mohd Wishal Nasrullah; Beti, Christyn Belaja; Zamri, Mohd Firdaus; Mohd Mervyn Dublin, Ahmad Alim; Dio, Douglas (2019)
TD Fratello Printing Samarahan (TD) have been recognized by all UiTM . Campus Samarahan 2. This is due to the location of the store is near to the UiTM Campus Samarahan 2 that located at Taman Desa Ilmu at Kota Samarahan. Services offered by TD includes photocopies services, shirt printing, medal printing, past year question and more. There are some problem that faced by TD that is the surrounding. The problems that related to the surrounding is the interior of the shop is to cramped that will make people movement limited to here and there. TD also needs to face with other competitor. The other competitor has more customer compared to TD that only receives a few of customers in a day. But, TD will find a way on solving those problems.